(untitled) (Research, Society and Development, 2020)
Introduction: Tracheostomy is a surgical procedure performed frequently on cancer patients, requiring special care by health professionals, family members and caregivers. Objective: To analyze the routine of care with the cleaning of the metallic cannula for tracheostomized cancer patients. Method: After approval by the Research Ethics Committee, the study was a preventive intervention with a qualitative approach carried out with health professionals at the Ophir Loyola Hospital (HOL) - Belém-PA, from April to September / 2019, with the realization a questionnaire of 9 open questions, passed on to professionals. For data analysis, Bardin’s content analysis technique was used, and the Iramuteq software performed the speech coding. Results: The population consisted of 25 participants: 8 nurses, 9 nursing technicians and 8 physiotherapists, with 8 professionals represented by nursing and physical therapy residents; and 17 were professionals and 8 were resident professionals. Iramuteq generated the word cloud in which the most evoked words are displayed graphically and the Descending Hierarchical Classification, which generated a corpus with 76.44% of use, and 6 classes of different text segments. Conclusion: It was possible to perform a routine analysis of how health professionals perform care with the metallic cannula, a significant percentage of professionals demonstrated to have knowledge incompatible with the literature, an educational video was created for the health professional to facilitate the transmission of hygienic care of the tracheostomy in beneficial to the patient.